Media and the environment in Malaysia: an analysis on news coverage of landslide disaster in Kuala Lumpur - Ahmad, Jamilah; Lateh, Habibah (Penerbit UKM, 2016)
Studies done on media reporting and the environment, particularly on natural disasters area less researched topic in Malaysia. This paper examines the representation of disaster news and analyses on how disaster news reports are being covered in local newspapers by taking a landslide case occurred at Taman Puncak Setiawangsa, Kuala Lumpur in December, 2012. The samples were taken from two local mainstream newspapers as a comparative study. Utusan Malaysia, being the major Malay newspapers in the country targets Malay readers, while The Star, an English-language daily, targets multi-ethnic and middle-class income readers. This study used quantitative and qualitative content analysis in identifying patterns of coverage by both newspapers. The analysis revealed that despite having their own principles, guidelines and ideologies; this study concludes that both newspapers have a lot of similarities in their reporting on this particular disaster. The main similarity is local environmental news is still predominantly presented as straight news.